The Influence of Tailor Communication Style and Clarity of Instagram Content @jahitkebaya_bdl on Customer Loyalty - Azura, Tabitha Rahma; Waskito, Budhi; Poyo, M. Denu (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of tailor communication style and Instagram content clarity on customer loyalty toward the @jahitkebaya_bdl account. Instagram has become a primary platform for digital marketing strategies, especially for small and medium enterprises like @jahitkebaya_bdl. In maintaining and increasing customer loyalty, two key factors examined in this research are the way tailors communicate with customers and the clarity of information conveyed through digital content on Instagram. This research employs a quantitative approach using a survey method through questionnaires distributed to Instagram followers of @jahitkebaya_bdl who have used its services more than twice. Data analysis is conducted using multiple linear regression to assess the relationship between the independent variables (communication style and content clarity) and the dependent variable (customer loyalty). The findings indicate that the tailor’s communication style significantly affects customer loyalty, particularly in terms of responsiveness, discussion ability, and professionalism. Content clarity on Instagram also plays a crucial role, as engaging visuals, easily understandable information, and transparency in pricing and ordering procedures enhance customer attachment to the brand. These findings contribute to digital marketing communication strategies, particularly in enhancing customer loyalty through optimized direct interactions and informative social media content.